Upper and lower Lebesgue classes of multivalued functions of two variables - Karlova, O. O.; Mykhailyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We introduce a functional Lebesgue classification of multivalued mappings and obtain results on upper and lower Lebesgueclassifications of multivalued mappings $F : X × Y \multimap Z$ for wide classes of spaces $X, Y$ and $Z$.